Ações mediadoras de alunos no fórum de um curso semipresencial de especialização - Cunha, Ana Lygia Almeida (2012)
This research is inserted in the realm of Applied Linguistics studies and aims to identify mediating actions performed by students in the 2007 class of the Specialization Course Teaching and Learning of the Portuguese Language for through the interpretation of messages posted in the discussion forum. During the activities developed in the course of Linguistic Pragmatics discipline, the finding that some students when interacting with their classmates acted as mediators led to the conception of this research whitch investigated the conditions that can make the student a mediator, thus contributing to the study of semiotic-pedagogic mediation that takes place in the online context. By starting from the Vygotsky s notion of mediation (1967/2008), the theoretical foundation of this study was grounded in authors interested in researching on the conditions under which interaction through forums are carried out in the online courses such as Gunawardena (1999), Garrison e Anderson (2003), Pallof e Pratt (2004), Coffin et al. (2005, 2006), Celani e Collins (2006), Collins (2008), Coll e Monereo (2010), Monereo e Pozo (2010), among others. The interpretation of messages posted by student mediators was based on the hermeneutic orientation supported by Ricoeur (2002, 2006, 2009), for whom the actions expressed in written texts can become an object of science. The research interpretation indicates the importance of the discussion forum as a privileged space for mediations made by students toward their peers